Widespread Doublecortin Expression in the Cerebral Cortex of the Octodon degus - Thomas van Groen; Inga Kadish; Natalija Popović; Natalija Popović; Natalija Popović; María Caballero Bleda; María Caballero Bleda; María Caballero Bleda; Beatriz Baño-Otalora; María Angeles Rol; María Angeles Rol; María Angeles Rol; et al. (Frontiers Media S.A., 2021)
It has been demonstrated that in adulthood rodents show newly born neurons in the subgranular layer (SGL) of the dentate gyrus (DG), and in the subventricular zone (SVZ). The neurons generated in the SVZ migrate through the rostral migratory stream (RMS) to the olfactory bulb. One of the markers of newly generated neurons is doublecortin (DCX). The degu similarly shows significant numbers of DCX-labeled neurons in the SGL, SVZ, and RMS. Further, most of the nuclei of these DCX-expressing neurons are also labeled by proliferating nuclear antigen (PCNA) and Ki67. Finally, whereas in rats and mice DCX-labeled neurons are predominantly present in the SGL and SVZ, with only a few DCX neurons present in piriform cortex, the degu also shows significant numbers of DCX expressing neurons in areas outside of SVZ, DG, and PC. Many areas of neocortex in degu demonstrate DCX-labeled neurons in layer II, and most of these neurons are found in the limbic cortices. The DCX-labeled cells do not stain with NeuN, indicating they are immature neurons.